Sand-based micro-bead nano anti-cracking high-strength floor mortar and pouring method

By adjusting the formula of sand-based microbead nano cracking resistance high-strength floor mortar, combined with the use of polymer emulsion interface agent, the problem of easy cracking of cement-based self-leveling mortar is solved, and the high-strength and crack resistance performance are improved and cost reduction is achieved. It is suitable for a variety of floor projects.

CN119822760APending Publication Date: 2025-04-15ZHEJIANG NANQI ECOLOGICAL ENVIRONMENTAL PROTECTION TECH CO LTD
0 Cites 0 Cited by

Patent Information

Application Number
CN202510015774.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing cement-based self-leveling mortar is prone to cracking, and the construction conditions are harsh, making it difficult to meet the requirements of high strength, wear resistance, flatness and finish, resulting in a decrease in market share.

Method used

By adjusting the formula in sand-based microbead nano crack resistance high-strength floor mortar, including the use of white high-strength high-belitt sulfur aluminate cement, quartz sand, ceramic microbeads and other components, combined with water reducing agent, defoaming agent, retarder, latex powder, coagulant, premature strength agent and expansion agent, a high-flow, premature strength agent and expansion agent, a high-flow, premature strength agent and a swelling agent are formed, and a polymer emulsion interface agent is used to improve adhesion and prevent cracking.

Benefits of technology

It has achieved the improvement of high strength and crack resistance of mortar, reduced the amount of cement and increased the amount of aggregate, significantly reduced the cost, and has environmentally friendly performance, and is suitable for various floor projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822760A_ABST
    Figure CN119822760A_ABST
Patent Text Reader

Abstract

The invention discloses sand-based microbead nano anti-cracking high-strength floor mortar and a pouring method, and relates to the field of building materials, the floor mortar comprises the following components by mass: 25%-40% of white high-strength high-belite sulphoaluminate cement, 11%-41.8% of quartz sand, 5.83%-26.51% of high-strength coarse river sand, 17.08%-27.0% of ceramic microbeads, 0.15%-0.6% of a water reducing agent, and the balance of water. The mortar is prepared from the following components in percentage by weight: 0.03%-0.05% of a defoaming agent, 0.2%-0.35% of a retarder hydroxypropyl methyl cellulose, 0.3%-0.45% of latex powder, 0.01%-0.04% of a coagulant, 5%-10% of an early strength agent and 0.3%-1% of an expanding agent. Through the synergistic effect of the terrace mortar formula, the use amount of cement is greatly reduced, the use amount of aggregate is increased, the mechanical property and the crack resistance are improved, and the cost is reduced exponentially; the cement-based mortar is prevented from easily cracking, and the construction condition difficulty is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, in particular to a sand-based micro-bead nano-anti-cracking high-strength floor mortar and a pouring method. Background Art

[0002] Cement-based self-leveling mortar is a technology introduced from abroad. The technology is very complicated, especially for cement-based self-leveling mortar for surface layer. The surface layer after pouring should have high strength and wear resistance, good flatness and smoothness, no cracks, and beautiful appearance. The difficulty is very great. The self-leveling cement-based mortar for surface layer in the current market is basically imported from abroad. Its cement-based gelling material is a ternary system of silicate cement, aluminate cement (or sulphoaluminate cement), and gypsum. The biggest difficulty is cracking. The construction conditions are demanding. Indoor construction even requires doors and windows to be closed. It is rare for it to be used in outdoor projects. Because the cracking problem is difficult to solve, the market share is getting lower and lower, especially the serious cracking problem of cement-based self-leveling mortar for surface layer is gradually being eliminated by the market.

[0003] Cement-based mortar is controlled by the elevation of the building, and is generally thinner in thickness. It is more prone to cracking, especially when subjected to traffic loads, because cracking is extremely common. The serious cracking problem of the floor brings serious economic losses to both the owner and the construction unit. Cement-based self-leveling mortar is urgently needed by the market, and it is also a cost-effective material for leveling the bottom layer of epoxy floor materials and artistic floor materials. Solving the cracking problem of cement-based mortar is a major technical problem that the floor industry has been dreaming of and urgently needs to solve. The present invention solves such problems and provides a cement-based self-leveling mortar with a low dimensional change rate, no cracks, controllable setting time, high fluidity, early strength and high strength performance, and environmental protection. Summary of the invention

[0004] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a sand-based micro-bead nano-anti-cracking high-strength floor mortar and a casting method. The present invention, through the synergistic effect of the floor mortar formula, greatly reduces the amount of cement and increases the amount of aggregate, improves the mechanical properties and crack resistance, and reduces the cost exponentially; solves the problems of easy cracking of cement-based mortar on the market and harsh construction conditions.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A sand-based micro-bead nano-anti-cracking high-strength floor mortar comprises, in percentage by mass: 25%-40% of white high-strength high-belite sulphoaluminate cement, 11%-41.8% of quartz sand, 5.83%-26.51% of high-strength coarse river sand, 17.08%-27.0% of ceramic micro-beads, 0.15%-0.6% of water reducer, 0.03%-0.05% of defoamer, 0.2%-0.35% of retarder hydroxypropyl methylcellulose, 0.3%-0.45% of latex powder, 0.01%-0.04% of coagulant, 5%-10% of early strength agent, and 0.3%-1% of expansion agent.

[0007] The aforementioned sand-based micro-bead nano-anti-cracking high-strength floor mortar, the water reducer includes: one or a combination of melamine, melamine-based water reducer or polycarboxylic acid water reducer.

[0008] The aforementioned sand-based micro-bead nano-anti-cracking high-strength floor mortar, the defoaming agent includes: one or a combination of hydrophobic silica, fatty amine or paraffin.

[0009] The aforementioned sand-based micro-bead nano-anti-cracking high-strength floor mortar, the coagulant includes: an accelerator with calcium aluminate or calcium fluoroaluminate as the main component or a quick-setting agent with silicate as the main component.

[0010] The aforementioned sand-based micro-bead nano-anti-cracking high-strength floor mortar, the early strength agent includes: one or a combination of calcium formate, lithium chloride or lithium carbonate.

[0011] The aforementioned sand-based micro-bead nano-anti-cracking high-strength floor mortar, the expansion agent is calcium sulfoaluminate CAS20#.

[0012] A method for pouring sand-based micro-bead nano-anti-cracking high-strength floor mortar comprises the following steps:

[0013] Step 1: Base layer, milling the base layer surface, repairing and cleaning;

[0014] Step 2: Apply the interface agent twice to form an interface agent layer;

[0015] Step three: Use sand-based micro-bead nano-anti-cracking high-strength floor mortar to lay on the interface agent layer to form a cement-based thick layer of self-leveling;

[0016] The sand-based micro-bead nano-anti-cracking high-strength floor mortar includes, according to the mass percentage: white high-strength high-belite sulphoaluminate cement 25%-40%, quartz sand 11%-41.8%, high-strength coarse river sand 5.83%-26.51%, ceramic micro-beads 17.08%-27.0%, water reducer 0.15%-0.6%, defoamer 0.03%-0.05%, retarder hydroxypropyl methylcellulose 0.2%-0.35%, latex powder 0.3%-0.45%, coagulant 0.01%-0.04%, early strength agent 5%-10%, expansion agent 0.3%-1%;

[0017] Step 4: Polish, grind, cure and seal the surface; or the surface is a decorative or functional surface layer.

[0018] The aforementioned method for pouring a sand-based micro-bead nano-anti-cracking high-strength floor mortar, if applied to the floor, the base layer is a cast-in-place reinforced concrete slab; if applied to the first floor floor, the base layer is a 120mm thick C30 fine stone concrete with a bidirectional φ8 steel mesh or an overhead structure slab; if applied to the basement, the base layer is a cast-in-place reinforced concrete raft slab, cement slurry is applied on the cast-in-place reinforced concrete, and then 30mm fine stone concrete is poured;

[0019] Fine stone: stone with a diameter of 5mm or less. It is generally irregular in shape, smooth in surface, soft in texture and easy to wear. Fine stone: mainly used in the batching of building materials such as concrete and asphalt to improve the density and strength of the material. The base layer is a cast-in-place reinforced concrete slab; if applied to the first floor, the base layer is a 120mm thick C30 fine stone concrete with a two-way φ8 steel mesh or an overhead structure slab; if applied to the basement, the base layer is a cast-in-place reinforced concrete raft slab, with cement slurry on the cast-in-place reinforced concrete, and then 30mm fine stone concrete is poured.

[0020] The aforementioned method for pouring a sand-based micro-bead nano-anti-cracking high-strength floor mortar, the interface agent is a polymer emulsion interface agent, and the polymer emulsion interface agent includes: one or more of vinyl acetate-ethylene copolymer emulsion or styrene acrylic emulsion. The polymer emulsion can form a continuous film on the surface of the base layer, increasing the adhesion and bonding strength of the base layer; the role of the interface agent: improve the bonding force: the interface agent can penetrate into the tiny pores on the surface of the base layer to form a firm bonding layer, enhance the bonding force between the base layer and the subsequent construction layer, and prevent hollowing, falling off and other problems. Seal the base layer: the interface agent can seal the pores and micro-cracks of the base layer, prevent premature penetration or loss of moisture, and ensure the uniform flow and curing effect of the construction layer. Remove impurities: The use of an interface agent before construction can effectively remove floating dust and other impurities on the original ground or after shoveling the ground, providing a clean and flat base layer for subsequent construction.

[0021] In the aforementioned method for casting a sand-based micro-bead nano-anti-cracking high-strength floor mortar, the cement-based thick layer self-leveling in step three is a 20mm thick C40 cement-based thick layer self-leveling.

[0022] The present invention is beneficial in that:

[0023] The present invention greatly reduces the amount of cement and increases the amount of aggregate through the synergistic effect of various components, improves mechanical properties and crack resistance, and reduces costs exponentially. The mortar has excellent properties such as acid corrosion resistance, small shrinkage, high tensile bonding strength, and fast coagulation and hardening. It is suitable for self-leveling floors, industrial floors, civil floors, artistic floors and other engineering applications in acid salt environments;

[0024] The cement-based mortar of the present invention has a low dimensional change rate, which fundamentally controls the generation of cracks. The free shrinkage rate of this product is only 1 / 10 to 1 / 8 of that of silicate cement, and the dimensional change rate of the prepared leveling mortar is -0.08% to +0.08%, which can effectively prevent the occurrence of cracks and hollowing;

[0025] The setting time of the cement-based mortar of the present invention is controllable: according to the specific construction scenario, the setting time can be controlled between 15 and 30 minutes, effectively avoiding the cracking problem caused by too fast setting time;

[0026] The cement-based mortar of the present invention has early high-strength performance, with a compressive strength of 2h≥30MPa, and a continuous increase in later strength, 28d≥60MPa, which accelerates the construction progress and has high later strength;

[0027] The cement-based mortar of the present invention has high fluidity and is easy to stir on site. When pouring, it can flow to the part to be poured without any external force or auxiliary measures and can be automatically leveled.

[0028] The cement-based mortar of the present invention has strong environmental protection performance, is odorless and pollution-free 、 No radioactivity; technical indicators comply with JC / T985-2005 standard. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a cross-sectional diagram of the construction process of the floor mortar of the present invention;

[0030] Meaning of the reference numerals in the figures:

[0031] 1 base layer, 2 interface agent layer, 3 cement-based thick layer self-leveling, 4 surface layer. DETAILED DESCRIPTION

[0032] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] The samples were prepared using the recipes and methods of the following examples.

[0034] Example 1: A sand-based micro-bead nano-anti-cracking high-strength floor mortar, which includes, in percentage by mass: 25% white high-strength high-belite sulphoaluminate cement, 41.8% quartz sand, 5.83% high-strength coarse river sand, 21.38% ceramic micro-beads, 0.15% water reducer, 0.03% defoamer, 0.2% retarder hydroxypropyl methylcellulose, 0.3% latex powder, 0.01% accelerator, 5% early strength agent, and 0.3% expansion agent.

[0035] Example 2: A sand-based micro-bead nano-anti-cracking high-strength floor mortar, comprising, in terms of mass percentage: 29% white high-strength high-belite sulphoaluminate cement, 34% quartz sand, 6.38% high-strength coarse river sand, 22.0% ceramic micro-beads, 0.3% water reducer, 0.04% defoamer, 0.25% retarder hydroxypropyl methylcellulose, 0.4% latex powder, 0.03% accelerator, 7% early strength agent, and 0.6% expansion agent.

[0036] Example 3: A sand-based micro-bead nano-anti-cracking high-strength floor mortar, comprising, in percentage by mass: 40% white high-strength high-belite sulphoaluminate cement, 11% quartz sand, 19.43% high-strength coarse river sand, 17.08% ceramic micro-beads, 0.6% water reducer, 0.05% defoamer, 0.35% retarder hydroxypropyl methylcellulose, 0.45% latex powder, 0.04% accelerator, 10% early strength agent, and 1% expansion agent.

[0037] Example 4: A sand-based micro-bead nano-anti-cracking high-strength floor mortar, comprising, in terms of mass percentage: 25.52% white high-strength high-belite sulphoaluminate cement, 11% quartz sand, 26.51% high-strength coarse river sand, 27.0% ceramic micro-beads, 0.4% water reducer, 0.05% defoamer, 0.25% retarder hydroxypropyl methylcellulose, 0.45% latex powder, 0.02% accelerator, 8% early strength agent, and 0.8% expansion agent.

[0038] The water reducing agent in the above embodiment is a melamine-based water reducing agent; the defoaming agent is hydrophobic silica; the coagulant is a coagulant with calcium aluminate and calcium fluoroaluminate as main components; the early strength agent is lithium chloride; and the expansion agent is calcium sulfoaluminate CAS20#.

[0039] Treatment of the original ground base:

[0040] 1. Use a floor scrubber to clean the floor to ensure that the original base is not loose, free of debris, and dense.

[0041] 2. Use a vacuum cleaner to clean the loose soil and impurities on the surface.

[0042] 3. Repair the honeycombs, holes and cracks in the base layer with the sand-based micro-bead special repair agent produced by Zhejiang Renchuang. If large areas of hollows are found, they should be completely removed and the base layer should be reconstructed to achieve a dense base layer.

[0043] 4. The base layer is solid and dense, and the compressive strength of concrete should not be less than 20MPA.

[0044] 5. Treatment of base expansion joints: Inject foam glue into the expansion joints, with the glue surface 20mm lower than the expansion joint surface. Apply the interface agent twice. The second coat can be applied only when the first coat is dry.

[0045] Leveling control points:

[0046] Set up a level to level the ground to be constructed. Check the flatness and set the spacing to one meter. Use the C40 special sand-based micro-bead material produced by Zhejiang Renchuang to repair the flatness.

[0047] Set up the demarcation area:

[0048] According to the different requirements of the drawings and renderings, draw lines for the parts with different color requirements, then paste double-sided adhesive strips (10*10mm) to set the dividing area.

[0049] A method for pouring sand-based micro-bead nano-anti-cracking high-strength floor mortar comprises the following steps:

[0050] Step 1: Base layer, milling the base layer surface, repairing and cleaning;

[0051] Step 2, brushing the interface agent twice to form an interface agent layer; brushing twice is a preferred method, and brushing once or multiple times is inspired by the present invention.

[0052] As a preferred embodiment, the interface agent is a polymer emulsion interface agent, and the polymer emulsion interface agent includes: one or more of vinyl acetate-ethylene copolymer emulsion or styrene acrylic emulsion. The polymer emulsion can form a continuous film on the surface of the base layer, increasing the adhesion and bonding strength of the base layer; the role of the interface agent: improve the bonding force: the interface agent can penetrate into the tiny pores on the surface of the base layer to form a firm bonding layer, enhance the bonding force between the base layer and the subsequent construction layer, and prevent hollowing, falling off and other problems. Seal the base layer: the interface agent can seal the pores and microcracks of the base layer, prevent premature penetration or loss of water, and ensure the uniform flow and curing effect of the construction layer. Remove impurities: The use of the interface agent before construction can effectively remove floating dust and other impurities on the original ground or after shoveling the ground, providing a clean and flat base layer for subsequent construction.

[0053] Step three, prepare the formula of the above embodiment, pour all the formula materials into special equipment together and stir until they are uniform and meet the good construction process requirements. It is recommended to use a forced mixer or a planetary mixer, and the mixing amount at one time shall not exceed 70% of the mixer capacity, and the water mixing time shall not be less than 3 minutes. It is strictly forbidden to use seawater or industrial wastewater for mixing; spread the sand-based micro-bead nano-anti-cracking high-strength floor mortar on the interface agent layer to form a 20mm thick C40 cement-based thick layer of self-leveling; air will be brought in during the mixing process, and special equipment will be used to defoam and level it before the construction ground begins to solidify. Use time: The materials mixed at one time should be used up as soon as possible, and the duration should not exceed 15 minutes. If the materials are left for too long, it is recommended to mix new materials for construction. Professional equipment is: forced mixer or planetary mixer.

[0054] Step 4: Grind the finished floor three times with a grinding robot to achieve the smoothness and flatness requirements.

[0055] Ground maintenance:

[0056] The finished product should be well protected and should be protected from direct sunlight, strong winds and airflows during maintenance. Generally, people can walk on it 8-10 hours after the construction is completed, and other operations can be carried out 24 hours a day.

[0057] Cutting and gluing

[0058] 1. 3-4 days after the construction is completed, the grid lines will be popped up on the ground. The grid lines should coincide with the expansion joints of the underlying cushion layer to avoid surface cracking caused by the expansion joints of the cushion layer. The width of the cut should be 3mm and the depth should be 10mm.

[0059] 2. After the dust is cleaned with a vacuum cleaner, use a glue gun to fill the seams with elastic structural sealant, and finally scrape it flat with a flat shovel.

[0060] Performance test indicators of cement-based self-leveling mortar for floor made of crack-resistant double-fast cement-based materials

[0061] Refer to the implementation standard JC / T985-2005 "cement-based self-leveling mortar for floor"

[0062]

[0063] The performance of Examples 1-4 was measured according to the standard:

[0064] Technical indicators

[0065]

[0066] From the above experimental results, it can be seen that the cement floor made by the formula and method of the present invention has a low dimensional change rate, which fundamentally controls the generation of cracks: the aggregate particle size of the base concrete is large, the general age is long, and the dimensional change rate is small. The surface leveling mortar must also ensure that it can be combined with the original concrete base under the condition of small deformation rate. This product uses white anti-cracking fast-setting fast-hardening high-belite sulphoaluminate cement, and the free shrinkage rate is only 1 / 10 to 1 / 8 of that of silicate cement. The size change rate of the prepared leveling mortar is -0.08% to +0.08%, which can effectively prevent the occurrence of cracking and hollowing. Higher tensile bonding strength: 28d tensile bonding strength ≥1.6Mpa, which can make the repair mortar and concrete base car-solidified together to control the occurrence of cracking and hollowing. The mortar is dense and has good anti-seepage and anti-freeze functions. Early strength and high strength: compressive strength 4h ≥ 15.0MPa, 1d ≥ 35.0MPa. With the increase of strength, drying is accelerated, and the moisture content of mortar decreases rapidly, which is conducive to the timely implementation of the next step of construction work and will greatly improve the construction efficiency. High fluidity: The construction operation of semi-dry hard leveling mortar on the market is very difficult and the construction efficiency is low; the initial fluidity of the mortar of this product is ≥ 280mm, and 30min ≥ 250mm. Workers can level it with a little spreading, which reduces labor intensity and improves construction efficiency and mortar flatness. Very high late strength: 28d compressive strength ≥ 45Mpa or more, can directly withstand heavy traffic loads.

[0067] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A sand-based micro-bead nano-anti-cracking high-strength floor mortar, characterized in that: In terms of mass percentage, it includes: white high-strength high-belite sulphoaluminate cement 25%-40%, quartz sand 11%-41.8%, high-strength coarse river sand 5.83%-26.51%, ceramic microbeads 17.08%-27.0%, water reducer 0.15%-0.6%, defoamer 0.03%-0.05%, retarder hydroxypropyl methylcellulose 0.2%-0.35%, latex powder 0.3%-0.45%, accelerator 0.01%-0.04%, early strength agent 5%-10%, and expansion agent 0.3%-1%.

2. The sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 1 is characterized in that: The water reducing agent includes: one or a combination of melamine, melamine-based water reducing agent or polycarboxylic acid water reducing agent.

3. The sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 1 is characterized in that: The defoaming agent comprises: one or a combination of hydrophobic silicon dioxide, fatty amine or paraffin.

4. The sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 1, characterized in that: The coagulant includes: a coagulant with calcium aluminate or calcium fluoroaluminate as main components or a quick-setting agent with silicate as main component.

5. The sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 1, characterized in that: The early strength agent includes: calcium formate, lithium chloride or lithium carbonate or a combination of the two or more thereof.

6. The sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 1, characterized in that: The expansion agent is calcium sulphoaluminate CAS20#.

7. A method for pouring sand-based micro-bead nano-anti-cracking high-strength floor mortar, characterized in that: The steps include: Step 1: Base layer, milling the base layer surface, repairing and cleaning; Step 2: Apply the interface agent twice to form an interface agent layer; Step three: Use sand-based micro-bead nano-anti-cracking high-strength floor mortar to lay on the interface agent layer to form a cement-based thick layer of self-leveling; The sand-based micro-bead nano-anti-cracking high-strength floor mortar includes, by mass percentage: 25%-40% of white high-strength high-belite sulphoaluminate cement, 11%-41.8% of quartz sand, 5.83%-26.51% of high-strength coarse river sand, 17.08%-27.0% of ceramic micro-beads, 0.15%-0.6% of water reducer, 0.03%-0.05% of defoamer, 0.2%-0.35% of retarder hydroxypropyl methylcellulose, 0.3%-0.45% of latex powder, 0.01%-0.04% of coagulant, 5%-10% of early strength agent, and 0.3%-1% of expansion agent; Step 4: Polish, grind, cure and seal the surface; or the surface is a decorative or functional surface layer.

8. The method for casting a sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 7, characterized in that: If applied to floors, the base layer is a cast-in-place reinforced concrete slab; if applied to the first floor, the base layer is a 120mm thick C30 fine stone concrete with a bidirectional φ8 steel mesh or an overhead structure slab; if applied to basements, the base layer is a cast-in-place reinforced concrete raft slab, with cement slurry applied on the cast-in-place reinforced concrete and then 30mm fine stone concrete poured.

9. The method for casting a sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 7, characterized in that: The interface agent is a polymer emulsion interface agent, and the polymer emulsion interface agent includes: one or more of vinyl acetate-ethylene copolymer emulsion or styrene-acrylic emulsion.

10. The method for casting a sand-based micro-bead nano-anti-cracking high-strength floor mortar according to claim 7, characterized in that: The cement-based thick layer self-leveling in step 3 is a 20 mm thick C40 cement-based thick layer self-leveling.